Korelasi Sistem Pembayaran Paylater dengan Perilaku Tiga Generasi dalam Kegiatan Ekonomi. Paylater : Keinginan atau Kebutuhan? - Azizah, Ine; Gina, Okta Nurul; Nabila, Sofa; Syahida, Syahla Aulia; Azkia, Zahra Nabilatu; Salsabila, Zahrah; Rozak, Rama Wijaya Abdul (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Generation X, millennials, and Gen Z really like e-commerce applications because of the rapid development of pay later in the digital era. This research aims to determine people's behavior in using paylater. Then, this research focuses on the essential needs of life or desires for sociality. This research uses a qualitative approach with the interview method. Research participants were carried out among people from different generations, and birth years. Namely, Generation X aged 40 to 55 years, the millennial generation aged 28 to 39 years, and Generation Z aged at least 18 to 27 years. The research results show that generation. Generation Z also occasionally fulfills their lifestyle. Based on this data, pay later is more widely used to meet living needs.